Fascist uchronias or post-fascist dystopias? Some reflections on two uchronic novels about fascism (Caleidoscopio. Revista de Italianistica de ADILLI, 2026)
This article explores the genre of uchronia, examining two uchronic Italian novels that address the theme of fascism. The first, Il fascio sulle stelle di Benito Mussolini by Massimo Mongai, analyzes the author’s meta-literary style and ability to create an alternative history that unexpectedly connects to our present. In the second, L’inattesa piega degli eventi by Enrico Brizzi, uchronia becomes a means to rewrite a history of postcolonial Italy, starting precisely from the former colonies. In both cases, we note how uchronia is not simply a genre linked to escapism, but becomes a means of critiquing contemporary Italy.
Keywords: Uchronia; Science-fiction; Fascism; Brizzi; Mongai